2013
DOI: 10.2302/kjm.2013-0003-re
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic Signalling: Pathophysiology and Therapeutic Potential

Abstract: The article begins with a review of the main conceptual steps involved in the development of our understanding of purinergic signalling, including non-adrenergic, non-cholinergic (NANC) neurotransmission; identification of ATP as a NANC transmitter; purinergic cotransmission; recognition of two families of purinoceptors [P1 (adenosine) and P2 (ATP/ADP)]; and, later, cloning and characterisation of P1 (G protein-coupled), P2X (ion channel) and P2Y (G protein-coupled) receptor subtypes. Further studies have esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 107 publications
(95 reference statements)
1
55
0
Order By: Relevance
“…This assertion has been confirmed in many diseases, such as IBS and interstitial cystitis [6]. Clinical and fundamental research had found that a variety of analgesic drugs have good efficacy during the treatment of visceral pain, thus showing a broad therapeutic potential [7,8]. The application of purinergic receptor antagonists has also expanded the treatment of visceral pain.…”
Section: Introductionmentioning
confidence: 93%
“…This assertion has been confirmed in many diseases, such as IBS and interstitial cystitis [6]. Clinical and fundamental research had found that a variety of analgesic drugs have good efficacy during the treatment of visceral pain, thus showing a broad therapeutic potential [7,8]. The application of purinergic receptor antagonists has also expanded the treatment of visceral pain.…”
Section: Introductionmentioning
confidence: 93%
“…Similar to growth factors, ATP exerts mitogenic effects on numerous cell types [315]. And similar to nucleotides, the growth factors epidermal growth factor (EGF) and vascular endothelial growth factors (VEGF) stimulated a variety of cellular responses, including cell proliferation and migration [316,317]. ATP and UTP were found to drive, in the identical cell type, intracellular signal cascades and cellular responses corresponding to those of EGF.…”
Section: Nucleotide Activates or Co-activates The Receptor Of Anothermentioning
confidence: 99%
“…Sensory neurons in dorsal root ganglion (DRG) express P2X receptors (P2XRs), ligand-gated cation channels that are assembled from at least seven different subunits (5,6,10,30). Spinal afferents predominantly display homomeric P2X3 and heteromeric P2X2/3 subtypes, and this system has been shown to be important in several animal models of visceral injury, including the urinary bladder (12, 24) and the colon (42).…”
mentioning
confidence: 99%